NANOSTRUCTURED LIPID CARRIERS AS A PROMISING DERMAL DELIVERY PLATFORM FOR ST. JOHN'S WORT EXTRACT: PRELIMINARY STUDIES - Yoana Sotirova; Stanila Stoeva; Rositsa Nikolova; Velichka Andonova (Peytchinski Publishing, 2023)
Purpose: Nanostructured lipid carriers (NLC) can improve the stability of various phytochemicals, so this research aimed to develop and employ such delivery systems for Hypericum perforatum extract containing the light- and oxygen-sensitive phloroglucinol hyperforin. Materials and methods: By varying the processing parameters and the solid and liquid lipids used, different NLC models were obtained via emulsification, followed by high-shear homogenization and ultrasonication. After characterization of the elaborated nanocarriers, those that exhibited optimal properties were loaded with St. John's wort extract by incorporating it in the lipid phase before emulsification and also studied. Results: The NLC models developed by prolonged ultrasonication demonstrated favorable characteristics regarding particle size, polydispersity index (PDI), and zeta potential (ZP). The physically stable during long-term storage nanosystems, which also showed a reduced degree of crystallinity of the solid lipid included, were loaded with St. John's wort extract. Of the carriers so-obtained, those developed by ultrasonication at ambient temperatures can be described as acceptably uniform systems (PDI from 0.23±0.01 to 0.27±0.01), comprising particles with dimensions below 200 nm, favorable ZP values (ζ > |30 mV|), and superior entrapment efficacy (EE) greater than 85%. Conclusion: In this research, different stable NLC dispersions were successfully developed. After the inclusion of the St. John's wort extract, the model possessing the highest EE (87.77±0.64%) was chosen as a carrier to conduct further studies evaluating its wound-healing potential.